Digital Marketing Training in Growing Entrepreneurial Interest in Package C Students at PKBM Anak Panah - Sari, Debby Synthia; Riyanto, Yatim; Widodo, Widodo (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
This research aims to equip students at PKBM Anak Panah Surabaya to have skills and entrepreneurship. By generating interest in business from an early age, it is hoped that it can prepare students to be independent. Learn to develop a business by using digital media as a marketing medium so that students are able to sell food and drinks. This research uses qualitative research methods by collecting data from participant observation, in-depth interviews and documentation. The results of this research are that the digital marketing training that has been carried out at PKBM Anak Panah plays an important role in shaping students' attitudes and interest in entrepreneurship. First, by having good knowledge and understanding of entrepreneurship, students can broaden their horizons and knowledge related to the world of business and entrepreneurship. Apart from fostering interest in entrepreneurship, entrepreneurship subjects for students at PKBM Anak Panah also have benefits in improving student learning achievement. It is hoped that the results of this research will provide a better understanding of online business optimization and interest in food and beverage businesses at PKBM Anak Panah.